Better Students Ask More Questions.
A curve has equation the follwing equation. y = 3x^3− 6x^2+4x+2. Show that the...
1 Answer | add yours
`y = 3x^3-6x^2+4x+2`
The gradient of a curve is given by the its first derivative as follows.
`y' = 9x^2-12x+14`
`=9[(x-12/18)^2 + 4/9 – (12/18)^2]` By completing square
We know that `(x-2/3)^2 >= 0` always for every x.
There for y' or gradient will be greater than or equal to 0.That means gradient never become negative.
Posted by jeew-m on August 31, 2013 at 11:26 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.